1991
DOI: 10.1070/qe1991v021n08abeh003963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atomic oxygen on the dissociation of molecular iodine and dissipation of the energy stored in the active medium of an oxygen–iodine laser

Abstract: We give examples of string compactifications to 4d Minkowski space with different amounts of supersymmetry that can be connected by spherical domain walls. The tension of these domain walls is tunably lower than the 4d Planck scale. The "stringy" description of these walls is known in terms of certain configurations of wrapped Dirichlet and NS branes. This construction allows us to connect a variety of vacua with 4d N = 4, 3, 2, 1 supersymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In a related earlier study, Zolotarev and co-workers concluded that the presence of O atoms was responsible for the low efficiency of an OIL system that was powered by the photolysis of O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In a related earlier study, Zolotarev and co-workers concluded that the presence of O atoms was responsible for the low efficiency of an OIL system that was powered by the photolysis of O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Iodine polyoxides (1) have been implicated in the atmospheric chemistry of iodine (2,3) in the reactivity of iodineozone mixtures (4), in the reactions between iodinecontaining compounds in the marine boundary layer (5,6), and in the mechanism of oxygen-iodine lasers (7). Methyl iodoperoxide is an interesting relevant species suggested to be involved in the mechanism of the self-reaction of CH 3 O 2 radicals formed in the photolysis of iodomethane (8) and the reactions of CH 3 O radicals with iodine monoxide (9).…”
Section: Introductionmentioning
confidence: 99%
“…Iodine oxides have been implicated in the atmospheric chemistry of iodine, , in the behavior of iodine−ozone mixtures, and in the mechanism of oxygen−iodine lasers . A recent review has drawn attention to the lack of information about any gas-phase iodine oxides except the simplest, IO, which is now well-characterized, and OIO, whose electronic and vibrational spectra have been obtained both in the gas phase and in a frozen argon matrix .…”
Section: Introductionmentioning
confidence: 99%
“…4 A recent review 5 has drawn attention to the lack of information about any gas-phase iodine oxides except the simplest, IO, which is now well-characterized, and OIO, whose electronic and vibrational spectra have been obtained both in the gas phase 6 and in a frozen argon matrix. 7 There are apparently no structural, vibrational, or thermochemical measurements available for other iodine oxides, and indeed the existence of some is speculative.…”
Section: Introductionmentioning
confidence: 99%